Phytochemical Analysis Of Cassia Obtusifolia, Cassia Auriculata, Tephrosia Purpurea, Helictres Isora And Centella Asiatica - HARSHAL A DESHPANDE; SANJIVANI R BHALSING (International Journal of Pharma and Bio Sciences, 2011)
It is an effort of making the analysis of the five species which are Cassia obtusifolia, Cassia auriculata, Tephrosia purpurea, Centella asiatica and Helictres isora. Ethanolic extract of leaves, stem, seeds and roots of Cassia obtusifolia and Cassia auriculata revealed the presence of alkaloids, flavonoids, tannins and anthroquinones while, it is found that the saponins were absent. Phytochemical analysis in the ethanolic leaf extract of Centella asiatica and Tephrosia purpurea showed the presence of flavonoids, tannins, saponins, while alkaloids were absent. The phytochemical constituents like tannins, flavonoids, anthroquinones and saponins were not detected, while, only alkaloids were detected in the ethanolic extract of fruit material of Helictres isora. The study establishes some concordance between the local medicinal applications of the plants investigated and their constituent phytochemical groups which are relevant to the pharmaceutical industry. The experiment carried out by using different plant parts of the plants revealed the presence of different types of phytochemical constituents.